Adverse outcome pathway-based assessment of pulmonary toxicity from the in vivo mixture of biocides dinotefuran and cetylpyridinium chloride - Yoon Cho; Mi-Kyung Song; Dong Im Kim; Min-Seok Kim; Kyuhong Lee (Heliyon)
Despite the increasing use of biocides globally and their widespread application in various formulations, the understanding of the toxicity of biocide mixtures remains limited. We previously identified cetylpyridinium chloride and dinotefuran as a potential binary biocidal combination associated with pulmonary fibrosis, based on two intersecting adverse outcome pathways (AOPs) using the molecular initiating events (MIE) modeling method and in vitro testing. These compounds activate or inhibit toll-like receptor 4 (TLR4) and peroxisome proliferator-activated receptor-gamma (PPAR-γ), which are associated with pathways having the potential to cause pulmonary fibrosis. In this study, we aimed to validate these AOPs by assessing the toxicity of cetylpyridinium chloride and dinotefuran mixture. Sixty C57BL/6 male mice were exposed to either dinotefuran or cetylpyridinium chloride or a mixture of the two via intratracheal instillation (ITI) to examine the synergistic effects of MIE and key events (KEs) within putative AOPs. Various parameters, including clinical and histopathological indicators, changes in body weight and organ weight, inflammatory cell distribution, and inflammatory cytokine expression in the bronchoalveolar lavage fluid (BALF), were analyzed. Additionally, key indicators such as TLR4, NF-κB, TNF-α were investigated to validate the mechanistic aspects of putative AOPs associated with pulmonary fibrosis. We observed significant changes in body weight and neutrophil count, recognized indicators of inflammation, along with inflammatory cell infiltrates, in the group exposed to the mixture of the two biocides. Moreover, increased levels of markers associated with epithelial–mesenchymal transition (EMT) and fibrosis (TNF-α, Acta2, IL-1β, and MMP9), as well as elevated levels of TGF-β, a common downstream signaling factor of TLR4 and PPAR-γ, were identified. Collectively, our findings highlight the potential toxic effects of a mixture of these two biocides in an in vivo model and confirmed the effective function of the putative AOP.